Assessment of a post-basic nursing education programme - P. du Rand; M.J. Viljoen (AOSIS, 2002)
A post-basic nursing education programme was introduced by the School of Nursing, University of the Free State, in 1999. The main aim o f the programme is to offe r vocationally directed specialisation and continuing educational opportunities to registered nurses. Qualifications, exit possibilities, the learning programme and the teaching- learning methods are described. A year after the programme was introduced student evaluation of the programme took place by means of questionnaires. The survey method was used to obtain the opinion of students via questionnaires. A convenience sample was applied and 82% of the questionnaires were returned. Although students appeared to be satisfied, they found some modules difficult. Twenty-three per cent found the lecturers helpful and considerate and 93% found contact with lecturers to be essential. The greatest advantage of the programme, however, is that it offers registered nurses an opportunity to qualify as clinical experts, because the programme focuses mainly on clinical specialisation. Tutorial staff are compelled by student estimates to examine the relevancy of curricula on a regular basis.